Potential Use of Cuticular Hydrocarbons in Estimating the Age of Blowfly Pupae Chrysomya megacephala (Diptera: Calliphoridae) - Rizoh, bin Bosorang; Zaini, Assim; Sulaiman, Hanapi; Fatimah, Abang (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Gas chromatography coupled with mass spectrometry (GC–MS) was used to determine the weathering time in cuticular hydrocarbon of pupae Chrysomya megacephala in sheltered condition. The results have shown that cuticular hydrocarbons (CHC) of the pupae were a mixture of n-alkanes, methyl-branched alkanes, and dimethyl-branched alkanes, with carbon chain length ranging from C19 to C39.The study presents the significant correlation between the changes pattern in relative abundance of several CHC and development phase in pupae. Further analysis with multiple linear regression indicated that several CHC compounds showed strong correlation to blowfly pupae age, which were then utilized to create a prediction equation for the age estimation. Finally, the application of the age-dependent model had revealed that estimated age correlated significantly with chronological age of samples C. megacephala., y = 0.97x + 0.092, R2 = 0.9698. The study concluded that, CHC have a potential to estimate age of immature C. megacephala, and possibly in other flies species, and might further be used to determine the PMI.